2014
DOI: 10.3354/dao02741
|View full text |Cite
|
Sign up to set email alerts
|

Bonamia parasites: a rapidly changing perspective on a genus of important mollusc pathogens

Abstract: Organisms of the genus Bonamia are intracellular protistan parasites of oysters. To date, 4 species have been described (B. ostreae, B. exitiosa, B. perspora and B. roughleyi), al though the status of B. roughleyi is controversial. Introduction especially of B. ostreae and B. exitiosa to naïve host populations has been shown to cause mass mortalities in the past and has had a dramatic impact on oyster production. Both B. ostreae and B. exitiosa are pathogens notifiable to the World Organisation for Animal Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 90 publications
0
48
0
Order By: Relevance
“…typically infect flat oysters Ostrea of the bivalve family Ostreidae (Engelsma et al 2014), with O. edulis considered as the type-host for B. ostreae. To rule out the possibility of a New Zealand incursion of O. edulis and, therefore with it, an incidental incursion of B. ostreae, the species of the oyster host was identified by DNA barcoding.…”
Section: In Situ Hybridisationmentioning
confidence: 99%
See 3 more Smart Citations
“…typically infect flat oysters Ostrea of the bivalve family Ostreidae (Engelsma et al 2014), with O. edulis considered as the type-host for B. ostreae. To rule out the possibility of a New Zealand incursion of O. edulis and, therefore with it, an incidental incursion of B. ostreae, the species of the oyster host was identified by DNA barcoding.…”
Section: In Situ Hybridisationmentioning
confidence: 99%
“…Bonamia microcells are small (typically 1−3 µm), uninucleated, and infect oyster hemocytes causing a disease known as bonamiosis (Hine & Jones 1994, OIE 2012. Molecular and ultrastructural studies have identified 4 Bonamia species from a number of hosts and locations throughout the world (Hine et al 2001 and to the European Union (OIE 2012, Engelsma et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The case of OsHV-1 mvar highlights an additional issue related to emerging diseases: it can be challenging to place [42,43]. One unexpected report was the detection of the parasite in O. edulis from Limfjorden, Denmark, a zone that gained its free status regarding bonamiosis in 2004 [44].…”
Section: The Paradox Of the List Of Notifiable Diseasesmentioning
confidence: 99%